A study of intrauterine infusion of human chorionic gonadotropin (hCG) before frozen-thawed embryo transfer after two or more implantation failures. (2nd January 2017) - Huang, Pinxiu; Wei, Lihong; Li, Xinlin
Abstract: Objective : To investigate the effect of intrauterine infusion of human chorionic gonadotropin (hCG) before frozen-thawed embryo transfer (FET) after two or more implantation failures (TIFs). Methods : The study was a prospective randomized single-blind study of 161 cycles in patients undergoing FET who had TIFs. The intervention group received an intrauterine injection of 1000 IU of hCG before embryo transfer (ET) ( n  = 62). A placebo group ( n  = 49) received an intrauterine injection of physiological saline before ET. A control group ( n  = 50) did not receive an intrauterine injection. Clinical pregnancy rates, abortion rates, and ongoing pregnancy rates were compared between the three groups. Results : The clinical pregnancy rates were 59.68%, 53.06%, and 32.00% in the hCG group, placebo group, and control group, respectively. The clinical pregnancy rates were significantly higher in the hCG and placebo groups than in the control group. There were no significant differences in the abortion rates among the three groups. Conclusion : An intrauterine administration of hCG before FET significantly improved the pregnancy rates after TIFs. But local injury caused by the operation of intrauterine perfusion may play an important role in improving clinical pregnancy rates.